The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1365-3040.2007.01746.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of heavy metals with the sulphur metabolism in angiosperms from an ecological point of view

Abstract: The metabolism of sulphur in angiosperms is reviewed under the aspect of exposure to ecologically relevant concentrations of sulphur, heavy metals and metalloids. Because of the inconsistent use of the term 'metal tolerance', in this review the degree of tolerance to arsenic and heavy metals is divided into three categories: hypotolerance, basal tolerance and hypertolerance.The composition of nutrient solutions applied to physiological experiments let see that the well-known interactions of calcium, sulphate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(111 citation statements)
references
References 287 publications
(626 reference statements)
3
108
0
Order By: Relevance
“…S has occupied an important place after N, P and K. It is the most important macronutrient for normal growth and development of plants with numerous biological functions 56,57 after N, P and K. S is known for its role in the formation of sulfur-containing amino acids (Cys and Met), and synthesis of proteins, vitamins, chlorophyll and GSH involved in stress tolerance. [58][59][60][61] It has been reported that adequate supply of S enhances the photosynthetic potential and growth of crop plants.…”
Section: Sulfur Assimilation and Uptakementioning
confidence: 99%
“…S has occupied an important place after N, P and K. It is the most important macronutrient for normal growth and development of plants with numerous biological functions 56,57 after N, P and K. S is known for its role in the formation of sulfur-containing amino acids (Cys and Met), and synthesis of proteins, vitamins, chlorophyll and GSH involved in stress tolerance. [58][59][60][61] It has been reported that adequate supply of S enhances the photosynthetic potential and growth of crop plants.…”
Section: Sulfur Assimilation and Uptakementioning
confidence: 99%
“…The sequestration of heavy metal cations by phytochelatin and the consecutive transport of the bis-glutathionato complexes into vacuoles seem to be the main route of heavy-metal detoxification in these organisms. Phytochelatins can be produced successfully in transgenic bacteria, leading to enhanced metal accumulation in the bacterial cytoplasm (3,11,28,69,72) without the compartmentation ability of a vacuole.Why do bacteria detoxify heavy metals mainly by efflux (49, 50) even though they should be able to sequester metals to the phytochelatin educt GSH? In GSH, two cysteine residues and four carboxyl groups should be able to form octahedral bisglutathionato complexes that are very stable (76).…”
mentioning
confidence: 99%
“…The main cellular thiol in cyanobacteria and proteobacteria is glutathione (GSH), which is absent in many other prokaryotes that contain other thiol compounds like mycothiol and ergothioneine (14,39). GSH (L-␥-glutamyl-Lcysteine-glycine) is essential in Saccharomyces cerevisiae for full cadmium resistance (18) and is the main substrate for the synthesis of the cadmium-binding polypeptide phytochelatin in many plants and fungi (11,13). GSH is synthesized from glutamate, cysteine, and glycine in two ATP-consuming steps (involving GshA and GshB) via the intermediate ␥-glutamylcysteine (␥EC).…”
mentioning
confidence: 99%